Integration of morphology, genetics, historical and ethnobotanical data: a case of an enigmatic Genista (Fabaceae) from Ischia Island (southern Italy) - de Castro, Olga; Vallariello, Roberta; Del Guacchio, Emanuele (Phytotaxa, 2013)
The vegetation and flora of Ischia Island (southern Italy) has fascinated several botanists over time, and its peculiar flora, especially on account of the volcanic environments, was carefully studied (e. g. by Gussone 1855, Ricciardi et al. 2004). Among the lesser known plants of the island, a species of Genista Linnaeus (1753: 709) sect. Ephedrospartum Spach (1844: 243) (Fabaceae) occurs in the locality of S. Montano (Lacco Ameno), in the north-western part of the island. It was first identified by Anzalone (1967: 694) as G. ephedroides De Candolle (1825: 210), while Ricciardi et al. (2004) reported it as G. gasparrinii (Gussone 1825: 11) Presl (1826: 19). According to Valsecchi (1993), G. gasparrinii is endemic to Sicily, growing in a restricted area of the Gallo Mountain, near Sferracavallo (Palermo province). Ricciardi et al. (2004) stated a possible introduction of G. gasparrinii from Sicily by G. Gussone, but no documentation for this hypothesis was provided. Brullo et al. (1992) indicated G. gasparrinii in the Gallo Mountain and in the Tyrrhenian Islands [Aeolian Islands and even Pontine Islands (Latium region, central Italy)]. The populations of these latter archipelagos were previously described as G. tyrrhena Valsecchi (1986: 145). On the basis of a specimen collected by B. Anzalone in S. Montano and published by Valsecchi (1993) as G. tyrrhena, Conti et al. (2007: 44) reported G. gasparrinii as endemic to Sicily and as an introduced species in Campania. Recently, Bacchetta et al. (2011) proposed two subspecies of G. tyrrhena: subsp. tyrrhena (endemic to Eolian Islands) and subsp. pontiana Brullo & De Marco in Bacchetta et al. (2011: 16), endemic to Pontine Islands. The literature data show that the occurrence of G. gasparrinii in Ischia Island needs a clarification.